2014
DOI: 10.1177/0951629813518129
|View full text |Cite
|
Sign up to set email alerts
|

Vacancies, vetting, and votes: A unified dynamic model of the appointments process

Abstract: Pundits, politicians, and political scientists alike often bemoan the long delays in filling both executive and judicial vacancies. However, most political science scholarship has ignored why executives delay nomination, instead focusing on why legislatures delay confirmation. In this article, I develop a formal model that seeks to explain the causes and consequences of both types of delay. By incorporating the effects of time, nominee competence, and nonpolicy incentives, the model provides a number of import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…Here, partisan and ideological dynamics will both point in the same direction, either jointly shortening or elongating the confirmation process. In these instances, due to its "team" aspect (e.g., Lee, 2008), partisanship should only exacerbate the effects of ideology (consistent with the logic in Hollibaugh, 2015c). With divided government, time until confirmation should increase due to the increased need for internal vetting to ensure confirmability relative to what is required under unified government.…”
Section: Theory and Hypothesesmentioning
confidence: 96%
See 1 more Smart Citation
“…Here, partisan and ideological dynamics will both point in the same direction, either jointly shortening or elongating the confirmation process. In these instances, due to its "team" aspect (e.g., Lee, 2008), partisanship should only exacerbate the effects of ideology (consistent with the logic in Hollibaugh, 2015c). With divided government, time until confirmation should increase due to the increased need for internal vetting to ensure confirmability relative to what is required under unified government.…”
Section: Theory and Hypothesesmentioning
confidence: 96%
“…For example, when the President and the Senate are at ideological or partisan odds, both executive and judicial nominees tend to endure longer confirmation periods and are more likely to be rejected (Asmussen, 2011;Bailey, 2007;Bell, 2002;Hartley & Holmes, 2002;Hollibaugh, 2015c;Jo, Forthcoming;McCarty & Razaghian, 1999;Shipan & Shannon, 2003). 1 Additionally, both the executive and judicial literatures have found that competent nominees experience greater confirmation probabilities and shorter delays (Basinger & Mak, 2010;Cameron, Cover, & Segal, 1990;Epstein, Lindstädt, Segal, & Westerland, 2006;Hollibaugh, 2015bHollibaugh, , 2015cShipan & Shannon, 2003; but see Lott, 2005, for a contrary claim). The importance of executive positions is also relevant, as nominees to the most important offices tend to be confirmed more quickly (Aberbach & Rockman, 2009;Chiou & Rothenberg, 2014;Krutz, Fleisher, & Bond, 1998;McCarty & Razaghian, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…1 The literature also considers the qualifications of executive agency appointments in detail. See Cohen, (1998), Edwards (2001), Heclo (1977), Hollibaugh (2013Hollibaugh ( , 2015c, Hollibaugh et al (2014), Krause and O'Connell (2010), Jo and Rothenberg (2012), and Lewis (2008aLewis ( , 2008b. 2 A number of alternative formal strategic models also consider executive appointments and delegation in the context of agenda-setting models.…”
Section: Note Smentioning
confidence: 99%
“… The literature also considers the qualifications of executive agency appointments in detail. See Cohen, (), Edwards (), Heclo (), Hollibaugh (2013, ), Hollibaugh et al (), Krause and O'Connell (), Jo and Rothenberg (), and Lewis (, ).…”
mentioning
confidence: 99%
“…How, then, might political nominees and appointees themselves affect public trust? Recent work on the politics of presidential appointments has focused on three broad criteria on which presidents decide who will serve in their administrations—responsiveness, competence, and patronage benefits (e.g., Bearfield ; Gallo and Lewis ; Heclo ; Hollibaugh ; Hollibaugh ; Hollibaugh, Horton, and Lewis ; Lewis ; Lewis ; Lewis ; Moe ; Parsneau ). Responsiveness, alternatively characterized as loyalty or ideological fidelity, captures the extent to which appointees are politically, philosophically, ideologically, or personally in sync with the president's needs and goals.…”
Section: Trust and Political Appointeesmentioning
confidence: 99%